Effects of a Blend of Live Yeast and Organic Minerals as an Alternative to Monensin on Intake, Digestibility, Performance and Beef Quality of Nellore Bulls Finished on Pasture with High Concentrate Supplementation - Soares, Maxwelder Santos [UNESP]; Batista, Luis Henrique Curcino [UNESP]; Oliveira, Ivanna Moraes; Issa, Hugo Aparecido Silveira; Cidrini, Iorrano Andrade [UNESP]; Ferreira, Igor Machado [UNESP]; Costa e Silva, Luiz Fernando; Koontz, Anne; Holder, Vaughn; Siqueira, Gustavo Rezende [UNESP]; Resende, Flávio Dutra de [UNESP] (MDPI, 2023)
Effects of a blend of live yeast and organic minerals as an alternative to monensin and inorganic trace minerals for beef cattle finished on pasture with high concentrate supplementation, on growth performance, intake, digestibility, liver trace mineral and carcass characteristics were evaluated. Forty-eight Nellore bulls were blocked by initial body weight and randomly assigned to one of the two experimental diets. The animals were raised in an experimental pasture divided into 12 paddocks equipped with an electronic system for monitoring individual feeding behavior and feed intake. Treatments were: (1) Monensin (MON), 30 mg/kg supplement dry matter of sodium monensin and trace minerals supplementation from inorganic sources; (2) AdvantageTM (ADV), 1.6 g/kg supplement DM of a blend of live yeast (Saccharomyces cerevisiae strains) and organic trace minerals. The use of ADV instead of MON led to greater supplement intake and greater intake of dietary components. Bulls fed ADV also had higher digestibility of dry matter, organic matter, crude protein and non-fiber carbohydrates. Bulls fed MON had a greater number of visits to the feeder, however with a shorter time spent feeding per visit. The use of ADV resulted in higher average daily weight gain, and feed efficiency was similar between treatments. In the carcass, ADV tended toward greater Longissimus muscle area. Liver Zn concentration tended to be lower in the ADV treatment. The use of ADV generated higher meat lightness and redness. In summary, the blend of live yeast and organic minerals can be an alternative to monensin and inorganic sources of trace minerals for beef cattle finished on pasture with high concentrate supplementation, without negative effects on supplement feed efficiency and with benefits to animal growth.
Keywords: carcass; chromium supplementation; ionophore; nutrition; yeast-based blend